Factores de Riesgos que Influyen en el Desempeño Laboral de los Docentes de la Institución Educativa Virginia Gómez en Ciénaga Magdalena Andrea Carolina - Mozo Juvinao, Andrea Carolina (Universidad Antonio Nariño, 2022)
The research on risk factors influencing the work performance of teachers at the Virginia Gómez educational institution in Ciénaga Magdalena aims to address the risk factors that influence the work performance of teachers at that educational institution, for which the project focuses on various variables such as; working conditions, unsafe work and illnesses in teachers. The type of methodology to be implemented in the research risk factors that influence the work performance of teachers at the Virginia Gómez educational institution in Ciénaga Magdalena is descriptive, qualitative and cross-sectional because each of the risk factors will be explained presented in the study population by performing a risk matrix according to the GTC 45 standard. The results of the research obtained through the hazard identification and risk assessment matrix, exposes the most latent risks within the Virginia Gómez Commercial Technical educational institution, which are biomechanical risks, psychosocial risks, physical risks, safety conditions and public risks; therefore it is necessary to take control measures to mitigate their negative impacts that may affect the development of work and the health of the worker.